2009
DOI: 10.1182/blood-2008-12-196014
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F mutation for the early diagnosis of Ph− myeloproliferative neoplasms in patients with venous thromboembolism: a meta-analysis

Abstract: Recent studies suggested that JAK2V617F mutation is frequent in patients with splanchnic vein thrombosis (SVT) but not in patients with other venous thromboembolic events (VTE). However, whether screening for the JAK2V617F mutation in VTE patients is justified remains unclear. Therefore, we performed a systematic review to assess the frequency of JAK2 mutation in VTE patients and the role of JAK2V617F mutation in the diagnosis of myeloproliferative neoplasms. MEDLINE and EMBASE databases were searched. Two rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 53 publications
5
143
1
1
Order By: Relevance
“…40 • JAK2V617F also occurs in other myeloid malignancies and is therefore useful as a clonal marker in the evaluation of otherwise unexplained BCR-ABL1-negative granulocytosis or monocytosis. 41 • JAK2V617F, but not JAK2 exon 12 or MPL mutations, 42 has been shown to identify occult MPN in patients with splanchnic vein thrombosis, 43 but the yield of mutation screening in the evaluation of nonsplanchnic thrombosis is very low. 44,45 • JAK2 mutations are present in virtually all patients with PV; therefore their screening is reasonable in the presence of characteristic symptoms of PV such as aquagenic pruritus or unexplained splenomegaly, even if the complete blood count picture is not suggestive of PV.…”
Section: Jak2 and Mpl Mutation Screening In Routine Clinical Practicementioning
confidence: 99%
“…40 • JAK2V617F also occurs in other myeloid malignancies and is therefore useful as a clonal marker in the evaluation of otherwise unexplained BCR-ABL1-negative granulocytosis or monocytosis. 41 • JAK2V617F, but not JAK2 exon 12 or MPL mutations, 42 has been shown to identify occult MPN in patients with splanchnic vein thrombosis, 43 but the yield of mutation screening in the evaluation of nonsplanchnic thrombosis is very low. 44,45 • JAK2 mutations are present in virtually all patients with PV; therefore their screening is reasonable in the presence of characteristic symptoms of PV such as aquagenic pruritus or unexplained splenomegaly, even if the complete blood count picture is not suggestive of PV.…”
Section: Jak2 and Mpl Mutation Screening In Routine Clinical Practicementioning
confidence: 99%
“…a.) und Thrombosen im Cerebralsinus [25][26][27][28]. Auch Mikrozirkulationsstörungen führen zu charakteristischen klinischen Symptomen (▶ Tab.…”
Section: Klinische Symptomeunclassified
“…They discovered that the mean prevalence of JAK2(V617F) mutation was 32.7 % in SVT patients and that this mutation was associated with increased risk of SVT (odd ratio, 53.98; 95 % CI, 13.10-222.45) and mean prevalence of this mutation is low in other VTE patients. Authors concluded that presence of JAK2 (V617F) mutation in SVT patients was associated with subsequent diagnosis of MPN in many patients and that routine screening of JAK2 (V617F) mutation appears to be indicated in SVT patients [33].…”
Section: Jak2 (V617f) Mutation Myeloproliferative Neoplasms and Splementioning
confidence: 99%